Experimental investigation on the reinforcement of a high-pressure jet grouting pile for an ultra-shallow tunnel in a strongly weathered stratum - Li, Pinpin; Huang, Xun; Lu, Feng; Qiu, Wenge; Liu, Huan; Li, Linlong; Wang, Yi; Chen, Zhenyu; He, Zhihao (Frontiers in Earth Science, 2023)
In this paper, the performance of high-pressure grouting material and consolidation body, the key parameters of tunnel surrounding rock reinforcement, and the field reinforcement effect are compared and studied. The results show that: (1) The compressive strength, elastic modulus, and seepage resistance of the consolidation body are related to the water-cement ratio. The permeability of the consolidation body increases with increasing water-cement ratio under the constant head; under the condition of a certain water-cement ratio, the strength increases with increasing cement content. To meet the construction requirements and the slurry stability, the water-cement ratio to small is appropriate. (2) Slurry pressure, rotary spray speed, and lifting speed on the single pile static load bearing capacity has a significant impact. Under the same static load conditions, the greater the slurry pressure, the lower the cumulative settlement value of the single pile, the cumulative settlement value increases less, and the amount of change in rebound is the same; With the increase in the rotational speed of rotary spray, the lower the cumulative settlement value of the single pile, the rate of change of the cumulative settlement value of the single pile decreases; With the increase in lifting speed, the cumulative settlement value of the single pile increases, the rate of change of the cumulative settlement value decreases. (3) The pile body cement soil is more uniform, high strength, and brittle, and the stratum where the slurry part is located is a loose powder clay layer and sandy layer. (4) After High-pressure jet grouting pile reinforcement, the top surrounding rock is more stable after the excavation of an ultra-shallow buried tunnel, the fissures between the surrounding rock are filled with cement soil consolidation, and the integrity is improved; The pile body also plays certain piles also play a certain role in stopping water; High-pressure jet grouting pile reinforcement to improve the integrity of the surrounding rock, played a role in consolidating the weak soil layer above the tunnel vault, creating conditions for the safe excavation of the shallow buried section of the tunnel.